2022
DOI: 10.1155/2022/7558825
|View full text |Cite
|
Sign up to set email alerts
|

Liquiritin Alleviates Depression-Like Behavior in CUMS Mice by Inhibiting Oxidative Stress and NLRP3 Inflammasome in Hippocampus

Abstract: Objective. Central inflammation is generally accepted to be involved in the pathology of depression. We investigated whether liquiritin exerts antidepressant effects by inhibiting central NLRP3 inflammasomes. Results. The behavioral despair model and chronic unpredictable mild stress (CUMS) model in mice were established to evaluate the antidepressant action of liquiritin. In the despair model study, liquiritin (40 mg/kg) administration reduced immobility time in tail suspension test (TST) and forced swimming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…P83 Umbelliferone (Zagaja et al, 2022) and P111 Neohesperidin (Chakraborty et al, 2021) have been reported to exhibit neuroprotective effects. P136 Liquiritigenin (Liu et al, 2022), P116 Tenuifoliside A (Dong et al, 2014), P73 Polygalaxanthone III (Du et al, 2022), P53 Loganin (Pan et al, 2021) and P151 Natsudaidain 3-(4-O-3-Hydroxy-3-Methylglutaroylglucoside) (Okuyama et al, 2017) have been shown to exert their effects through various mechanisms, including changes in neurotransmitter levels, increased cAMP levels and amelioration of locomotor hyperactivity…”
Section: Discussionmentioning
confidence: 99%
“…P83 Umbelliferone (Zagaja et al, 2022) and P111 Neohesperidin (Chakraborty et al, 2021) have been reported to exhibit neuroprotective effects. P136 Liquiritigenin (Liu et al, 2022), P116 Tenuifoliside A (Dong et al, 2014), P73 Polygalaxanthone III (Du et al, 2022), P53 Loganin (Pan et al, 2021) and P151 Natsudaidain 3-(4-O-3-Hydroxy-3-Methylglutaroylglucoside) (Okuyama et al, 2017) have been shown to exert their effects through various mechanisms, including changes in neurotransmitter levels, increased cAMP levels and amelioration of locomotor hyperactivity…”
Section: Discussionmentioning
confidence: 99%
“…[ 58 ] Another major component of this herb, liquiritin, exerts antidepressant effects by reducing oxidative stress and neuroinflammation. [ 59 ] B falcatum L. has antidepressant effects associated with increased serum nerve growth factor and brain-derived neurotrophic factor, [ 60 ] relieving oxidative stress, regulating the HPA axis, and protecting neurons. [ 61 ] Furthermore, the antidepressant activity of this herb has been implicated in the central adrenergic mechanism [ 62 ] the serotonergic and noradrenergic systems.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that Glycyrrhizin may exert its antidepressant effects by inhibiting the activation of microglial cells, suppressing the release of pro-inflammatory cytokines, and protecting dendritic spine morphology in the hippocampal region ( Chen et al, 2020 ). Research also suggests that Glycyrrhizin exerts its antidepressant effects in part by inhibiting the levels of cytokines triggered by the NLRP3 inflammasome, highlighting the role of antioxidative stress and the inhibition of NLRP3 inflammasome activation in antidepressant properties of Glycyrrhizin ( Liu et al, 2022a ). Glycyrrhizin is applicable in various depression models, as it can reduce the levels of FSH and estradiol E2 in the serum, improve the decreased 5-HT and NE levels in the hypothalamus, and increase the levels of monoamine neurotransmitters, thereby ameliorating depressive-like behavior in perimenopausal rats ( Lan et al, 2020 ).…”
Section: Research On the Antidepressant-like Effects Of The Active In...mentioning
confidence: 99%